Comparison of six commercially available SARS-CoV-2 antibody assays—Choice of assay depends on intended use - Nilsson, Anna Christine (Int J Infect Dis, 2021)
OBJECTIVES: Evaluate six commercial serological assays for detection of IgA, IgM or IgG SARS-CoV-2 antibodies in different disease severities. METHODS: Three lateral flow tests (LFTs) (Acro IgM/IgG, CTK IgM/IgG, Livzon IgM/IgG) and three ELISA assays (Euroimmun IgA and IgG, Wantai IgM) were included. Application was evaluated using samples from 57 patients with a positive SARS-CoV-2 reverse transcription polymerase chain reaction, stratified according to disease severity. Specificity was assessed using historical samples from 200 blood donors. RESULTS: While IgM LFTs failed to detect SARS-CoV-2 antibodies in 37–84% of non-hospitalised patients, the Wantai IgM ELISA detected antibodies in 79%. The Euroimmun IgG ELISA detected antibodies in 95% of non-hospitalised patients. IgA, IgM and IgG ELISA levels were initially low, increased over time, and correlated with disease severity. LFT sensitivity declined in samples taken >28 days after symptom onset/resolution. The Livzon IgG LFT had the highest specificity (98.5%), followed by the Euroimmun IgG ELISA (96.2%). The specificity for Euroimmun IgA ELISA improved (≥97.5%) using a custom cut-off value (4.0). CONCLUSIONS: The sensitive and semi-quantitative ELISA assays are most appropriate for serologic detection of SARS-CoV-2 infection in mild cases. Livzon LFT and Euroimmun ELISA had the highest specificity among the IgG assays, making them most suitable for seroprevalence studies.